DOES BELONGING MATTER?: EXPLORING THE ROLE OF SOCIAL CONNECTEDNESS AS A CRITICAL FACTOR IN STUDENTS’ TRANSITION TO HIGHER EDUCATION - Pym, June; Goodman, Suki; Patsika, Natasha (PINS-Psychology in Society, 2025)
Widening access to Higher Education throughout the world has meant an increase in the number of students who do not necessarily have the types of capital that universities require. This means an increasing need to engage with the issues that separate students from connecting with their modes and places of learning. This paper describes a successful Academic Development programme that is focused on equity students in the Commerce Faculty at the University of Cape Town (South Africa). The programme actively promotes academic and affective factors that will contribute toward affirming students’ identity and developing a learning community. The paper reports on the results of a research project that combined qualitative and quantitative research methods to investigate how fostering social connectedness impacts on the transition of students to higher education and their academic performance.